Study guides

Q: Factorise 2x plus 7 plus 5?

Write your answer...

Submit

Related questions

2x(y - 3) + 7(y - 3) = (2x + 7)(y - 3)

(x - 3)(2x - 7)

Y = 2x-5 and Y = 2x plus 7 is a linear system which intersects at points (-2,2)

6x - 8 + 2x - 5 = 7 - 2x ?

4x - 7 = 2x + 5 2x - 7 = 5 2x = 12 x = 6.

14x2 - 39x - 35 = (7x + 5)(2x - 7)

(The original question was misphrased.) 4x-7 = 2x+5 resolves as 2x-7 = 5 2x = 12 x = 6

5x - 3 + 2x + 7 = ?7x + 5 = ?

f(x)= (x-7) /(-2x+7)(2x+5) set -2x+7=0 -2x=-7 x=7/2 set 2x+5=0 2x=-5 x=-5/2 x=7/2 and x=-5/2 are vertical asymptotes.

2x + 5 = 7 - 4x ie 2x + 4x = 7 - 5 ie 6x = 2 x = one third.

6x-8+2x-5 = 7-2x 6x+2x+2x = 7+8+5 10x = 20 x = 20/10 x = 2

7x + 6 - 4x = 5 + 2x + 7 subtract 6 from both sides and combine the 5 and 7 on the right: 7x - 4x = 2x + 6 subtract 2x from both sides and combine the 7x and -4x on the left: x = 6

x + 2x + 5 = x +19 3x + 5 = x +19 3x - x = 19 - 5 2x = 14 x = 7

2x + 52 = 7 2x + 25 = 7 2x = 7 - 25 2x = -18 x = -18/2 x = -9

3x+7=2x-5 x=-12

= 5x plus 7.

p2+10d+7

-2x^2 + 17x - 35 = 0 = (-2x + 7)(x - 5) x =7/2 or 5

3x + 2 + 2x = 7; 3x + 2x = 5x, so 5x + 2 = 7; 7-2=5, so 5x=5. 5x divided by 5 and 5 divided by 5 equals 1, so x equals 1.

4x2 + 28x + 49 = 4x2 + 14x + 14x + 49 = 2x(2x + 7) + 7(2x + 7) = (2x + 7)(2x + 7) or (2x + 7)2

2x+12-3x = 5 2x-3x = 5-12 -x = -7 x = 7

7

7

-3x+7=2x-18 ---> 7+18=2x-3x ----> 25=5x ----> x=5

Simplifying 4x + -5 = 2x + 7 Reorder the terms: -5 + 4x = 2x + 7 Solving -5 + 4x = 7 + 2x Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -5 + 4x + -2x = 7 + 2x + -2x Combine like terms: 4x + -2x = 2x -5 + 2x = 7 + 2x + -2x Combine like terms: 2x + -2x = 0 -5 + 2x = 7 + 0 -5 + 2x = 7 Add '5' to each side of the equation. -5 + 5 + 2x = 7 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = 7 + 5 2x = 7 + 5 Combine like terms: 7 + 5 = 12 2x = 12 Divide each side by '2'. x = 6 (your answer)